Liburnia as a mansion of Central Europe : memoirs and literary testimony by Ivana Brlić-Mažuranić - Jurdana, Vjekoslava (Array, 2019)
Liburnia is a geographic region along the eastern coast of Istria, bordered by Učka, Preluk and Plomin Bay. Its linguistic and cultural dimensions are strongly determined by its geological, geographical and political uniqueness. In the middle of the 19 th century, this area began to develop as an elite Central European tourist destination. Within the Austro- Hungarian Monarchy, Opatija was a well-known Liburnian winter and summer resort. Members of the royal families, composers and writers came to visit Opatija, including the famous Croatian writer Ivana Brlić-Mažuranić. Based on documents recently discovered in Ivana’s correspondence, this paper documents and depicts her stays in Liburnia, which have not been researched and written about before. Moreover, the recent literature related to tourist and cultural history of Liburnia emphasizes numerous famous guests who visited this area, but fails to mention Ivana Brlić-Mažuranić. In addition to Ivana’s correspondence, this paper analyses her portrayal of Liburnia based on her memoirs and lyrical prose. Her work is an expressive testimony of the development of the culture of travel of the 19 th century Central-European upper class. Ultimately, it is a valuable portrayal of Liburnia at the end of the 19 th and beginning of the 20 th centuries, which was the time of its intense tourist expansion.